The green June beetle (Cotinis nitida) (Coleoptera: Scarabaeidae): local variation in the beetle's major avian predators and in the competition for mates. Issue 11 (26th March 2016) - Alcock, John
Abstract: The green June beetle ( Cotinis nitida ) was observed in northern Virginia for a second and third flight season. The study yielded some results that were consistent with earlier findings, namely that mate-locating beetles were vulnerable to attack by avian predators and matings occurred primarily early in the flight season. Novel findings included the following: (1) blue jays ( Cyanocitta cristata ) were the major predators, not common grackles ( Quiscalus quiscala ), (2) some jays appeared to selectively prey on female beetles, (3) competition for mates among male beetles could be so intense that some males attempted to copulate with already mated (unreceptive) females, and (4) the sex ratio of the beetle population feeding on wild blackberries remained near equality late in the flight season despite the fact that the sex ratio of the population of beetles at the emergence site became highly female-biased over time.